Share
Notifications

View all notifications
Advertisement

If Q is the Mean Proportional Between P and R, Show That: Pqr (P + Q + R)3 = (Pq + Qr + Rp)3 - Mathematics

Login
Create free account


      Forgot password?

Question

If q is the mean proportional between p and r, show that: pqr (p + q + r)3 = (pq + qr + rp)3

Solution

Given, q is the mean proportional between p and r.
⇒ q2 = pr

L.HS = `pqr(p + q + r)^3`

`= qq^2 (p + q + r)^3`        [∵ q^2 = pr]

`= [q(p +  q + r)]^3`

`= (pq + q^2 + qr)^3`

`= (pq + pr + qr)^3`      ` [∵ q^2 = pr]`

= R.H.S

  Is there an error in this question or solution?
Advertisement

APPEARS IN

 Selina Solution for Concise Mathematics for Class 10 ICSE (2020 (Latest))
Chapter 7: Ratio and Proportion (Including Properties and Uses)
Exercise 7(B) | Q: 10 | Page no. 94
Advertisement
If Q is the Mean Proportional Between P and R, Show That: Pqr (P + Q + R)3 = (Pq + Qr + Rp)3 Concept: Proportions.
Advertisement
View in app×